2001
DOI: 10.1007/s004180100291
|View full text |Cite
|
Sign up to set email alerts
|

Protein phosphatase 2Cα expression in normal human tissues: an immunohistochemical study

Abstract: Protein phosphatase (PP2Cα) is a member of the mammalian serine threonine-specific protein phosphatases family. We produced monoclonal antibodies against the recombinant PP2Cα and evaluated the immunoreactivity of normal human tissues. The reactivity was strong in normal skin, the digestive tract, lung, kidney, breast, prostate, endocrine glands, and brain, while it was moderate in the ovary, testis, and liver. Epithelial cells revealed high levels of PP2Cα expression, but stromal cells, including fibroblasts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…In the present study we also provide evidence that PPM1A and PPM1B redundantly dephosphorylate the α-subunit of AMPK. Although these isoforms are closely related (75 % identity), they were shown to be distinctly localized in cells [15,19,41], raising the possibility that they might act on AMPK heterotrimeric complexes at different subcellular locations within cells. Recently, Voss et al [33] reported that PPM1E is a protein phosphatase that acts on AMPK.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study we also provide evidence that PPM1A and PPM1B redundantly dephosphorylate the α-subunit of AMPK. Although these isoforms are closely related (75 % identity), they were shown to be distinctly localized in cells [15,19,41], raising the possibility that they might act on AMPK heterotrimeric complexes at different subcellular locations within cells. Recently, Voss et al [33] reported that PPM1E is a protein phosphatase that acts on AMPK.…”
Section: Discussionmentioning
confidence: 99%
“…PP2Cα was expressed mainly in different epithelial cell types in organs and tissues including the skin, lungs, kidney, breast, digestive tract, endocrine glands, testis, prostate, ovary, uterus, brain, lymph nodes and bone marrow. Human endothelial cells, smooth muscle cells and extracellular matrix contained no or very little PP2Cα 77 . In contrast with the other Ser/Thr protein phosphatases, how the activity, localization and substrate specificity of PP2C are governed is not clear 76 .…”
Section: Regulation Of Ampk In Endothelial Cellsmentioning
confidence: 99%
“…As an example of the predictive value of this assay, analysis in the Ppm1a-CreER T2 line is described here, in which CreER T2 expression is driven by the promoter of the ubiquitous "protein phosphatase 1A, magnesiumdependent, alpha isoform" gene (Lifschitz-Mercer et al, 2001). Also described is the Vil1-CreER T2 mouse line, in which the recombinase is targeted to the epithelial cells of the intestinal crypts (Meseguer and Catterall, 1987;Pinto et al, 1999;Robine et al, 1997).…”
Section: Specificity and Efficiency Of Cre Expressionmentioning
confidence: 99%